A Look at Big Data and the Conjoint Analysis - Linares-Barbero, Manuela (2015)
This article aims to expose the use of Big Data in Conjoint Analysis or analysis of sets (trade-off analysis). Companies  are always developing new products, which is aided by the use of market data in in order to research and identifying the preferences of their targeted customers. Currently, the cluster analysis is one of the most used tools within market research. This is because it helps cut costs in the process. Through descriptive research, various investigations using conjoint analysis can be reviewed to gather information and simulate software tools like Sawtooth, taking advantage of Big Data technology. It can be concluded that transactional and social information used with Big Data can efficiently aid researchers if used in conjunction with the conjoint analysis.